Inquiry into IT Pricing - Australia. Parliament. House of Representatives. Standing Committee on Infrastructure and Communications (Canberra : Parliament of Australia, House of Representatives, 2012)
"On 24 May 2012 the Committee resolved to inquire into IT price discrimination, following a request from the Minister for Broadband, Communications and the Digital Economy, Senator Stephen Conroy."
Title from title screen (viewed on 30 July 2012)
Text and grapchis.
Mode of access: Available online. Address as at 20/9/12
Selected for archiving
Keywords: Information technology -- Economic aspects -- Australia; Price discrimination -- Australia; Australian